ANALISIS CARGO OFF SPEC DI MT.GUNUNG KEMALA MENGGUNAKAN METODE FISH BONE ANALYSIS - Jepi Harpiansyah Ramdhani; Rizal Rochmansyah; I Kadek Laju; Natanael Suranta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Tankers is an important role in supporting the distribution of fuel oil. During the transportation process, the quality of the cargo is a crucial aspect because it must meet the specified requirements. However, in practice, there are often problems with cargo quality known as cargo off spec, which is a condition where the cargo does not meet the required quality standards. This study aims to determine the causes and solutions as well as prevention of cargo off spec on MT. Gunung Kemala. The method used in this study is descriptive qualitative, with the research location on the MT. Gunung Kemala ship. The data used is primary data obtained directly through interviews and observations, while secondary data is obtained from ship documents or related official reports on board the ship. This study also used data collection techniques such as observation, interviews, and documentation. It also used the fishbone analysis method for data analysis. The results of this study show that the causes of cargo off spec on MT. Gunung Kemala were due to the physical condition of the tanks and the characteristics of the cargo being carried. It was also caused by the intertank process carried out by the ship. Efforts to overcome cargo off spec were carried out by using free water treatment with a Wilden pump. Preventive measures that can be taken include improving infrastructure maintenance, specifically the implementation of tank cleaning to remove sludge that is a source of contamination. Optimization of intertank handling procedures and strict supervision are carried out through sampling and testing methods from several points.